Electroplating Method on Copper (Cu) Substrate with Silver (Ag) Coating Applied - Rini Selly; Siti Rahmah; Hafni Indriati Nasution; Ricky Andi Syahputra; Moondra Zubir (Indonesian Journal of Chemical Science and Technology (IJCST), 2020)
Knowing about metal coating (electroplating) is the electrodeposition of coatings or coatings attached to the electrodes to protect the substrate by giving surface properties and dimensions different from the base metal or finishing technique, by coating metal that is easily corroded (corrosion) with metals that are resistant to corrosion with electrical and chemical engineering. Whereas in Indonesian society the technique for metal coating is very familiar with the name of the gilding technique. In ancient times before electroplating and gilding were discovered to avoid corrosion of metals, the incorporation of metals such as copper with tin into bronze, copper with zinc into brass in addition to being resistant to corrosion also added to the beauty of color. Among the alloys above bronze is the oldest alloys that have been used by humans. With the development of the times, more modern gilding techniques were found to be a more practical method, namely electroplating, gilding with electrical and chemical processes that make metals resistant to corrosion. Metal coating is a scientific field which is one of the applications of electro chemical technology. Very closely related to the material science and technology, surface chemistry, physical chemistry, to the engineering. Various metals can be plating. The various metals are classified into five groups: tumbal coatings, decorative-protective coatings, engineered metal coatings, rare-use metals, and various types of alloys. All of these have their own characteristics, both advantages and disadvantages.